An efficient protocol for transferring selectable marker gene gus/gusplus into cassava plants (Manihot esculenta Crantz) mediated by bacteria Agrobacterium tumefaciens - Lan, Do Hai; Son, Le Van; Binh, Le Tran (Academia Journal of Biology, 2017)
In this study, to evaluate the ability to accept transgenes of the two cassava cultivars KM94 and KM140, which are grown widely in Viet Nam, A. tumefaciens bacterial strains C58/pGV2260, EHA105 and LBA4404 containing vector pCB-gusplus or pPIPRA558 haboring selectable marker gene gus/gusplus, were co-inoculated with explants from four selected sources, including (1) immature leaves, (2) shoot apexes, (3) callus, and (4) somatic embryo cotyledons. Transgenic explants were selected using three antibiotics kanamycin, neomycin, and paromomycin, at concentrations of 25, 50, 75, and 100 mg/l , based on nptII gene. These experiments were conducted to optimize conditions for transferring gus gene to cassava plant. The transformation efficiency was evaluated based on the percentage of X-gluc positive stained explants 10 days after infection, somatic embryos, regenerated shoots and whole regenerated plants. The highest transformation efficiency was achieved when using A. tumefaciens C58/pGV2260, carrying expression vector pCB-gusplus, and cotyledons of cultivars KM94. In this protocol, cotyledons were cut into small pieces, then cultured on the callus induction medium for 2 days and submerged in bacterial suspension, supplemented with 100 μM AS, with shaking at 50 rpm for 15 minutes. Explants were then co-cultured on somatic embryo induction medium supplemented with 150 μM AS in the darkness for 2 days. Explants were then transferred to selective callus induction medium with 50 mg/l kanamycin for 3 - 4 weeks, followed by the culture on selective shoot induction medium with the same kanamycin concentration. Shoots, with 2 - 3 leaves, were transferred to a selective rooting medium to establish whole plants.